The Potential for The Development of Augmented Reality Media to Increase Student Understanding of Earthquake Material - Zakirman, Zakirman; Sukmayadi, Dodi; Widiasih, Widiasih; Risha, Nurfa (Jurnal Ilmiah Profesi Pendidikan, 2023)
Along with the development of technology, the use of smartphones in teaching and learning activities has become one of the most influential innovations in the world of Education, especially in physics learning. Learning media is needed to make it easier for students to understand physics concepts, but media that can visualize abstract concepts clearly have not been developed much. As an alternative media, Augmented Reality was chosen as a solution to this problem. This type of research is descriptive qualitative and aims to describe the potential for the development of augmented reality media to increase students' understanding of earthquake material. Data collection techniques using questionnaires. The questionnaire was made using G-Form containing six question items, each of which required a response in the form of a checklist or description in each item answer column according to the respondent's opinion. The questionnaire was distributed online to respondents who were students of Universitas Pendidikan Ganesha and Universitas Terbuka. The sample was randomly selected as many as 206 students who had attended the lecture wave. Research conclusions can be drawn after analysis of questionnaires filled out by respondents. Based on data analysis, it can be understood  that the media / learning resources on wave material so far used by lecturers are powerpoint (PPT) with a percentage of 14%, the media used so far is considered by students to be less attractive 22%, the obstacles encountered by students are at most visualizing wave forms 27%, the media that students consider appropriate for wave material is through visualization / illustration with a maximum percentage of 61%,  so that AR media is considered to have the potential to make wave material interesting and easy to understand.